Sugar-Sweetened Beverages Contribute Significantly to College Students’ Daily Caloric Intake in Jordan: Soft Drinks Are Not the Major Contributor - Hiba Bawadi (3436379) (2019)
Sugar sweetened beverages (SSBs) are caloric-dense and associated with poor diet quality which may result in weight gain and obesity. Obesity is an independent risk factor for several chronic diseases. This study aimed to (1) assess the consumption level of SSBs among college students in Jordan and (2) examine the relationship of consumption level to body weight. The current study is a cross-sectional study conducted on 967 college students (55.3% males and 44.7% females). Consumption of SSBs was assessed using validated questionnaires. SSBs were classified into four major categories (hot drinks, fruit drinks, energy drinks, and soft drinks). Anthropometric measurements of the participants including body weight, height, and waist circumferences were recorded. Male students consumed more calories from SSBs compared to female students (p = 0.016). The mean contribution of SSBs to daily energy intake among college students was 480 kcal with the highest contribution from sugar sweetened hot drinks and fruit drinks. A significant positive relationship was found in BMI (p = 0.006) and waist circumference (p = 0.030) for participants consuming calories from SSBs. In conclusion, beverages with added sugar contribute substantially to the daily energy intake of college students in Jordan. Other Information Published in: Nutrients License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nu11051058